2017
DOI: 10.1080/01616412.2017.1363349
|View full text |Cite
|
Sign up to set email alerts
|

The study of memory and executive dysfunction in patients infected with Helicobacter pylori

Abstract: Background Infectious agents are considered as potential causes of Alzheimer's disease. Recently, evidence of a high prevalence of Helicobacter pylori (H. pylori) infection in patients with Alzheimer's disease has been observed. The aim of this study was to investigate memory and executive function in H. pylori positive persons not suffering from Alzheimer's or other marked cognitive disorders. Methods This is a cross-sectional study. A total 140 participants were selected using purposive sampling from the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…It was revealed by a prospective, longitudinal study that children with a history of bacterial meningitis were at greater risk of impairment in executive ability (Anderson et al, 2004). A study that employed a total 140 participants who were selected using purposive sampling from the patients within the age group of 18-60 years old at Tehran in 2016 found that Helicobacter pylori infection increases the prevalence of memory and executive dysfunction (Rezvani et al, 2017). To the best of our knowledge, our study is the first to demonstrate the corresponding associations of selected taxa with specific domains of cognitive functioning among hypertension patients.…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed by a prospective, longitudinal study that children with a history of bacterial meningitis were at greater risk of impairment in executive ability (Anderson et al, 2004). A study that employed a total 140 participants who were selected using purposive sampling from the patients within the age group of 18-60 years old at Tehran in 2016 found that Helicobacter pylori infection increases the prevalence of memory and executive dysfunction (Rezvani et al, 2017). To the best of our knowledge, our study is the first to demonstrate the corresponding associations of selected taxa with specific domains of cognitive functioning among hypertension patients.…”
Section: Discussionmentioning
confidence: 99%
“…9 Regarding cognition, H. pylori status was associated with lower baseline performances as reported by previous cross-sectional studies. 7,8 Beyond baseline cognitive scores, this study prospectively examined the risk of incident dementia according to H. pylori status. During the 7-year follow-up, H. pylori-positive participants had an increased risk of dementia, independently of various dementia risk factors [HR = 1.70], the risk of AD being still stronger [HR = 2.85].…”
Section: Discussionmentioning
confidence: 99%
“…Even though H. pylori prevalence has tended to decrease these last decades, cross‐sectional studies hint toward a high prevalence of this infection in older adults with cognitive disorders 7–9 . Likewise, longitudinal studies report different rates of negative cognitive outcomes in H. pylori ‐positive individuals or those treated for the infection 10–12 .…”
Section: Introductionmentioning
confidence: 99%
“…Except for many upper gastrointestinal diseases, some extragastric diseases are also associated with H. pylori infection, such as atherosclerosis (AS), nonalcoholic fatty liver disease (NAFLD), diabetes, obesity, Alzheimer's disease (AD), chronic obstructive pulmonary disease (COPD), skin diseases, and blood diseases. [8][9][10][11][12][13][14] In particular, H. pylori infection can affect the cardiovascular system, and there is a causal relationship between H. pylori infection and cardiovascular events. 15 The role of H. pylori infection in the development of AS and its clinical prognosis has received attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researches consistently reported that H. pylori is considered a pathogenic factor for gastric cancer. Except for many upper gastrointestinal diseases, some extragastric diseases are also associated with H. pylori infection, such as atherosclerosis (AS), nonalcoholic fatty liver disease (NAFLD), diabetes, obesity, Alzheimer's disease (AD), chronic obstructive pulmonary disease (COPD), skin diseases, and blood diseases 8‐14 . In particular, H. pylori infection can affect the cardiovascular system, and there is a causal relationship between H. pylori infection and cardiovascular events 15…”
Section: Introductionmentioning
confidence: 99%